The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1098/rspb.2014.2925
|View full text |Cite
|
Sign up to set email alerts
|

Geographical variation in mutualistic networks: similarity, turnover and partner fidelity

Abstract: Although species and their interactions in unison represent biodiversity and all the ecological and evolutionary processes associated with life, biotic interactions have, contrary to species, rarely been integrated into the concepts of spatial b-diversity. Here, we examine b-diversity of ecological networks by using pollination networks sampled across the Canary Islands. We show that adjacent and distant communities are more and less similar, respectively, in their composition of plants, pollinators and intera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
225
4
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(257 citation statements)
references
References 52 publications
6
225
4
2
Order By: Relevance
“…Empirical studies have shown a high variability of mutualistic plant–animal interactions across years3031, suggesting a high flexibility in these networks. In contrast, recent studies have highlighted the importance of partner fidelity in both antagonistic and mutualistic ecological networks3233 that might be associated with a high degree of trait matching between interacting species in these networks3435. According to these studies, the flexibility of interactions will be constrained in ecological networks under future conditions, suggesting that unconstrained rewiring of interactions is unlikely even for generalized mutualistic networks.…”
Section: Discussionmentioning
confidence: 98%
“…Empirical studies have shown a high variability of mutualistic plant–animal interactions across years3031, suggesting a high flexibility in these networks. In contrast, recent studies have highlighted the importance of partner fidelity in both antagonistic and mutualistic ecological networks3233 that might be associated with a high degree of trait matching between interacting species in these networks3435. According to these studies, the flexibility of interactions will be constrained in ecological networks under future conditions, suggesting that unconstrained rewiring of interactions is unlikely even for generalized mutualistic networks.…”
Section: Discussionmentioning
confidence: 98%
“…To explore similarity between sites, we calculated pairwise Sorenson dissimilarity indices for plant species observed in the three sites (see Trojelsgaard et al, 2015) where values close to 0 indicate very similar community composition and values close to 1 indicate very distinct communities. For our sites, Sorenson values ranged from 0.13 to 0.25, indicating very similar plant composition.…”
Section: Methodsmentioning
confidence: 99%
“…2B) will do so wherever and whenever they meet. While studies of ecological networks to date have mostly been concerned with the distribution of interactions within locations, and less so with the variation among locations, there is now ample evidence that ecological interactions vary in space and time (Poisot et al 2012;Trøjelsgaard et al 2015). It is in resolving how interaction structure varies with the environment (see Poisot et al 2012Poisot et al , 2015 that DNA barcodes will reveal their true potential.…”
Section: Towards Network Of Ecological Network In Space and Timementioning
confidence: 99%